Effect of pre-task music on sports or exercise performance - Smirmaul, B. P. (The Journal of Sports Medicine and Physical Fitness, 2017)
INTRODUCTION: Pre-task music is a very common strategy among sports competitors. However, as opposed to in-task music, the scientific evidence to support its ergogenic effects on either sports or exercise performance is limited. This brief review critically addresses the existing literature investigating the effects of pre-task music on sports and exercise performance, focusing on the methods and results of experimental studies, and offers basic and practical recommendations.